Neuroimmune Mechanisms as Novel Treatment Targets for Substance Use Disorders and Associated Comorbidities - Namba, Mark D.; Leyrer-Jackson, Jonna M.; Nagy, Erin K.; Olive, M. Foster; Neisewander, Janet L. (Frontiers in Neuroscience, 2021)
Recent studies examining the neurobiology of substance abuse have revealed a significant role of neuroimmune signaling as a mechanism through which drugs of abuse induce aberrant changes in synaptic plasticity and contribute to substance abuse-related behaviors. Immune signaling within the brain and the periphery critically regulates homeostasis of the nervous system. Perturbations in immune signaling can induce neuroinflammation or immunosuppression, which dysregulate nervous system function including neural processes associated with substance use disorders (SUDs). In this review, we discuss the literature that demonstrates a role of neuroimmune signaling in regulating learning, memory, and synaptic plasticity, emphasizing specific cytokine signaling within the central nervous system. We then highlight recent preclinical studies, within the last five years when possible, that have identified immune mechanisms within the brain and the periphery associated with addiction-related behaviors. Findings thus far underscore the need for future investigations into the clinical potential of immunopharmacology as a novel approach towards treating SUDs. Considering the high prevalence rate of comorbidities among those with SUDs, we also discuss neuroimmune mechanisms of common comorbidities associated with SUDs and highlight potentially novel treatment targets for these co-morbid conditions. We argue that immunopharmacology represents a novel frontier in the development of new pharmacotherapies that promote long-term abstinence from drug use and minimize the detrimental impact of SUD co-morbidities on patient health and treatment outcomes.